Devout : losing my faith to find myself - Archuleta, David, 1990- (Gallery Books, 2026)
"At just seventeen, David Archuleta rose to national fame as the runner-up on American Idol season seven, captivating millions with his angelic voice. Behind the scenes, however, he was struggling with a truth he feared would destroy everything: he was attracted to men--and a devout member of The Church of Jesus Christ of Latter-day Saints. In Devout, David takes you inside his deeply personal journey as a closeted Mormon teen turned international pop star, torn between faith, fame, and identity. From dealing with the pressures of being on a hit television show to a domineering father who controlled every aspect of his career--even being banned from the show's set--David reveals the emotional abuse and inner turmoil that he says plagued his childhood. This ... memoir reflects on David's ventures with American Idol, a tour with Demi Lovato, and a two-year sabbatical as a missionary in South America, charting his path through heartbreak, estrangement, three engagements, thoughts of suicide, and finally, his courageous decision to leave the Mormon Church in order to live authentically as a queer man."--